Pembukaan Majlis Taklim Keba' Kalam (Kedungrejo Diba' Kajian Islam) - Machnunah Ani Zulfah; Ata Badrul Hayaa; Muh Syarif Hidayatulloh; Wahyu Nuryati; Raka Ansar Razak (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The conditions that actually occur in today's society for the formation of a good Muslim personality are very difficult, because there have been many deviations from norms, ethics, behavior as a form of mental or moral decline in personality which is very incompatible with the ethics of Islamic teachings or the eastern culture of the Indonesian nation. What's more, this applies to the younger generation's hopes for the future of the nation and it is very ironic that this applies to pupils or students who receive education in formal institutions where moral values ​​have often been abandoned. Therefore, it is considered very necessary if this behavior development is carried out, one of which is through learning moral beliefs for students, as well as in family life, because learning moral beliefs contains learning materials that direct students to behave in a commendable manner and avoid behavior. the despicable one. After knowing and understanding the problems that exist in Kedungrjo village, the KKN group from KH University. A. Wahab Hasbullah collaborated with the youth of the mosque and all community leaders in Kedungrejo village to conduct a study on the theme of morals through the example of the prophet. This activity is used as a routine study every month in Kedungrejo village with the name KEBA' KALAM study (Kedungrejo Diba' Islamic Study). This target is determined based on the needs and objectives of the Majlis Ta'lim Keba' Kalam activities, namely for children and teenagers. The method used in this approach is direct observation and interviews with village officials, elders and community leaders, as well as the local community. This akhlaqul karimah study event went smoothly, many of the TPQ students enthusiastically attended the event until the end.